Initiatives to Enhance Research-Practice Integration in the Swiss Sport System - Philipp Röthlin (Current Issues in Sport Science)
The integration of research and practice remains a challenge in elite sport. While scientific insights are increasingly valued, their implementation lags behind. Bridging this gap requires targeted funding programs, well-defined roles, and innovative projects that connect research and practice. This symposium highlights three distinct approaches aimed at fostering this integration.